NUMERICAL MODELLING OF STORM SURGES BY 3D CIRCULATION MODEL - Phung, Nguyen Ky; Tan, Le Manh (Vietnam Journal of Marine Science and Technology, 2006)
NUMERICAL MODELLING OF STORM SURGES BY 3D CIRCULATION MODEL